STUDY OF THE OPTICAL PROPERTIES OF ZnTe THIN FILMS FOR USE IN PHOTOVOLTAIC CELLS - Bhatti, M. Tariq; Raza, M. Ishaq; Rana, Anwar Manzoor (Journal of Research (Science), 2004)
Zinc Telluride (ZnTe) belongs to II-VI binaries and is an important solar cell material because it has an optimum band gap ≅ 2.26eV required for the absorbance of solar cell spectrum. For the present study, ZnTe thin films were deposited onto thoroughly cleaned glass substrates kept at room temperature by vacuum evaporation. These films were annealed at temperatures of 100°C, 200°C, 300°C and 375°C for 15 minutes in air atmosphere. The optical properties of as evaporated and annealed films were then studied. A slight rise in band gap energy was observed due to annealing caused by the grain growth and improved crystallinity.